1998
DOI: 10.1006/viro.1998.9090
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Stem-Loops in the RNA Packaging Signal of the Moloney Murine Leukemia Virus

Abstract: The retroviral RNA genome is targeted for incorporation into the nascent virion particle by the psi region, a specific block of RNA sequences near the 5' end. A number of deletions and linker insertion mutations were introduced into the psi region of cloned DNA of the Moloney murine leukemia virus, and the mutants were introduced into cells in culture and tested for their ability to direct the assembly of virions and the packaging of viral RNA. Only a small portion of the psi region was important for packaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…The SL355-4 mutation disrupts the base and top of the SL-D stem. This mutation reduced RNA incorporation into virions by more than 100-fold and severely disrupted replication ability, almost abolishing viral spread as detected by reverse transcriptase assay (17). A second SL-D mutation, G364A, changed the first G in the SL-D tetraloop to an A.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The SL355-4 mutation disrupts the base and top of the SL-D stem. This mutation reduced RNA incorporation into virions by more than 100-fold and severely disrupted replication ability, almost abolishing viral spread as detected by reverse transcriptase assay (17). A second SL-D mutation, G364A, changed the first G in the SL-D tetraloop to an A.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, it was of interest to test how mutations previously shown to impair RNA encapsidation in vivo would affect the interaction with MMLV Gag in the yeast three-hybrid system. A report from Fisher and Goff (17) described an analysis of the effects of MMLV ⌿ mutations on in vivo RNA encapsidation and viral spread. In this study, SL-C and SL-D mutations were shown to have dramatic effects on viral RNA packaging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Psl-3 and Psl-4 are positioned at the same distance from the primer binding site in RD114, as are two psls DIS-1 and DIS-2 of the MLVs. Moreover, two GACGhairpins downstream from DIS-2 are implicated in the dimerization and packaging of MLV-RNA (Mougel and Barklis 1997;De Tapia et al 1998;Fisher and Goff 1998;Kim and Tinoco 2000;Badorrek et al 2006). Such GACGhairpin motifs are also found in RD114 RNA (as well as in BaEV and PcEV), with GACG-sequences at nucleotide positions 336-339 and 371-375, respectively (see Fig.…”
Section: Discussionmentioning
confidence: 99%